HERP depletion inhibits zearalenone-induced apoptosis through autophagy activation in mouse ovarian granulosa cells. (February 2019) - Chen, Fenglei; Wen, Xin; Lin, Pengfei; Chen, Huatao; Wang, Aihua; Jin, Yaping
Highlights: ZEA decreases cell viability and increases cell apoptosis in ovarian granulosa cells in a dose-dependent manner. Autophagy and ER stress cooperate in cell apoptosis in ovarian granulosa cells that is induced by ZEA. HERP depletion inhibits ZEA-induced cell apoptosis in ovarian granulosa cells through autophagy activation and apoptosis inhibition. Abstract: HERP is an endoplasmic reticulum (ER) membrane protein and is strongly induced by stress conditions. A recent study has indicated that HERP cooperates in apoptosis during zearalenone (ZEA) treatment. However, regulatory mechanisms and the role of HERP in ZEA-induced apoptosis remain elusive in ovarian granulosa cells. In this study, MTT and flow cytometry assays demonstrated that ZEA gradually decreased cell viability and increased apoptosis in granulosa cells in a dose-dependent manner. Western blot analysis showed that ZEA significantly activated autophagy by upregulating LC3-II. Chloroquine (CQ) significantly increased LC3-II and induced granulosa cell apoptosis. Moreover, Western blot analysis showed that ZEA inhibited the mTOR and ERK1/2 signaling pathways. Furthermore, we found that ZEA activated ER stress by upregulating the ER stress-related proteins GRP78, HERP and CHOP. 4-PBA significantly decreased GRP78, HERP, CHOP and LC3-II. In addition, knockdown of HERP (shHERP) significantly protected ovarian granulosa cells from apoptosis induced by ZEA. We found that HERP depletion activated autophagy and ERK1/2 signaling pathways, while it inhibited the mTOR and caspase-dependent mitochondrial signaling pathways. In summary, autophagy and ER stress cooperated in apoptosis induced by ZEA; HERP depletion inhibits ZEA-induced apoptosis of ovarian granulosa cells through autophagy activation and apoptotic pathway inhibition.